PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY DISERTAI MEDIA AUDIO-VISUAL UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN BIOLOGI SISWA KELAS XI IPA 5 SMA NEGERI 7 SURAKARTA TAHUN PELAJARAN 2011/2012 - Wardhani, Irma Yuniar; Sajidan, Sajidan; Maridi, Maridi (Pendidikan Biologi, 2012)
ABSTRACT ? The aim of this research is improve  biology learning quality  for  teacher performance,  learning facilities,  classroom climate, student?s  science  attitude in class, and student motivation of learning in student class XI Sains 5 SMA Negeri 7 Surakarta.  The research is classroom action research. The steps of research include planning, acting, observing, and reflecting. The collecting data of research uses questionnaire, observation, and interview. The research uses triangulation as validation data. The research uses descriptive as analytic data.  The acts of research contain  three cycles. The result in cycles I, II and III describes that mean of observation data in  the classroom  for  aspect  teacher performance,  classroom climate, student?s science attitude and students motivation in learning have been increase for every cycles and achieve of target ? 75% in cycles III,  the utility of learning facilities in the classroom as well have been optimal. In addition, this research also uses interview  and the result of interview shows that student motivation can improve after acts of research end, attitude of students  can improve after act of research end, and conditioning of class can more interesting after acts of research end. The conclusion of research describes that  the implementation of learning model cooperative type two stay two stray with media audio-visual can improve  biology  learning quality for  teacher performance,  learning facilities, classroom climate, student?s science attitude, and motivation of learning in student class XI Sains 5 SMA Negeri 7 Surakarta. Keywords: learning model cooperative type two stay two stray, media audio-visual, biology learning quality